Handbook of Bereavement Research: Consequences, Coping, and Care. 2001
DOI: 10.1037/10436-018
|View full text |Cite
|
Sign up to set email alerts
|

Processes of grieving: How bonds are continued.

Abstract: so completely." Indeed, a professional concern with bereavement-how survivors live on after the death-arose in the modem West at precisely the time that public concem with the afterlife-how the dead themselves live on-waned (AriPs, 1981;Walter, 1996a). It is perhaps not surprising that academic models of bereavement have focused on the bereaved individual rather than on the relations between bereaved people and those they have lost. That bereaved people maintain a bond with their dead has been recognized by tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
79
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(80 citation statements)
references
References 31 publications
1
79
0
Order By: Relevance
“…People in these circumstances can be reluctant to talk about such things as belief in paranormal phenomena, continuing bonds (Klass & Walter, 2001), or unpredictable bouts of distress. The expert companion is constant as a non-judgmental listener to all these experiences.…”
Section: Tolerance Of the Strange Non-rational And Ambiguousmentioning
confidence: 99%
“…People in these circumstances can be reluctant to talk about such things as belief in paranormal phenomena, continuing bonds (Klass & Walter, 2001), or unpredictable bouts of distress. The expert companion is constant as a non-judgmental listener to all these experiences.…”
Section: Tolerance Of the Strange Non-rational And Ambiguousmentioning
confidence: 99%
“…Continuing involvement via conversation with others and its impact on grief reactions are understudied (Klass & Walter, 2001). An exception is work by Bonanno et al (2004), who found that at 6 months postloss, the bereaved talked about their spouse from once a week to two or three times a week; at 18 months postloss, they talked about their spouse about once a week.…”
Section: Continuing Involvement and Emotional Resolutionmentioning
confidence: 99%
“…A number of writers (Baker, 2001;Klass & Walter, 2001;Normand, Silverman, & Nickman, 1996;Silverman et al, 1992) have discussed a variety of strategies that children, adolescents, and adults use to maintain connections with the deceased. These range from talking about and to the deceased, using the deceased as a moral referent to experiencing the deceased's presence, keeping objects of the deceased, and becoming a "living legacy."…”
mentioning
confidence: 99%
“…Theories on maintaining attachments and "continuing bonds" with the deceased acknowledge the interconnected part of ourselves. Klass and Walter (2001) trace the religious movement from Catholicism to the Protestant reformation and with it "the rejection of human bonds that continued after death" (p. 434). Catholicism allowed for more direct contact between the deceased and the living.…”
mentioning
confidence: 99%